Kansas and Deutschland: Two Places, One Slimy Problem - Bechtel, Sarah; Bramble, Chloe; Hook, Ezekiel; Silence, Sophia; Yoder, Grayson (Kansas State University. Dept. of Modern Languages., 2025)
In this project, we wanted to learn more about an ecological problem that is facing both Kansas (where we live) and Germany (the country we are studying in our course). We found that the zebra mussel (Zebramuschel) presents similar problems in both places. This invasive species has been spreading westward from the Caspian Sea since the 1800s and reached Kansas in 2003. We looked at why zebra mussels are a problem, how water infrastructure developments and shipping have contributed to the spread of this invasive species, potential solutions that have not worked over time, and the fact that prevention is currently the best measure.
Kirmser Undergraduate Research Award - Group category, honorable mention
Keywords: Zebra Mussel (Zebramuschel); Kansas; Invasive Species; Germany